Editorial - Goh, Pauline Swee Choo; Ratnavadivel, Nagendralingan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
One of the most talked about themes in the history of education is the need for improvement and change. The drive for educational improvements and change in Malaysia have raised important questions pertaining to emerging and competing paradigms and programs of research on teaching, teacher learning, and teaching and learning in various subject matters. However, teacher educators are situated as ‘frontliners’ to work together with educational stakeholders to improve teacher education, teaching, and learning with bold, fresh, creative and empirically sound concepts, strategies and outlooks – all imperative for understanding the challenges and developing useful solutions towards educational improvement and change. Motivated by these common understandings, this issue brings together experienced scholars in the education arena to share their ideas drawn from personal understandings of their specialisation and research.